The Association Between Sociability and COVID-19 Pandemic Stress - Luo, Peihao; LaPalme, Matthew L.; Cipriano, Christina; Brackett, Marc A. (Frontiers in Psychology, 2022)
The COVID-19 pandemic threatened our physical health, alongside our mental and social wellbeing. Social distancing requirements, which are necessary to mitigate the spread of COVID-19, increased social isolation by limiting social interactions that are an essential part of human wellbeing. In this study, we examined the stress caused by COVID-19 early on in the pandemic through the lens of sociability among a large sample of preservice educators (N = 2,183). We found that individuals who have higher sociability (including deriving joy from social interactions and using social support to manage emotions) experienced greater COVID-19 stress. This study also contributed to prior literature which has sought to relate pandemic-related stress to demographic group differences. We found no significant relationship between demographic membership (gender, race, and sexual orientation) and COVID-19 stress. This study is among the first, however, to demonstrate that vulnerability to pandemic stress varies as a function of sociability. Implications of these findings and ways people can better cope with pandemic isolation are discussed.